What Can Lexical Tone Training Studies in Adults Tell Us about Tone Processing in Children? - Antoniou, Mark; Chin, Jessica L. L. (Frontiers in Psychology, 2018)
A growing number of studies on the acquisition of lexical tone by adult learners have revealed that factors such as language background, musical experience, cognitive abilities, and neuroanatomy all play a role in determining tone learning success. On the basis of these findings, it has been argued that the effectiveness of tone learning in adulthood depends on individual differences in these factors. However, it is not clear whether similar individual differences play an analogous role in tone learning in childhood. Indeed, relatively few studies have made comparisons between how adults and children learn lexical tones. Here, we review recent developments for tone learning in both adults and children. The review covers tone training in a range of contexts, including in naive listeners, in native speakers of other tone languages, in listeners with varying levels of musical experience, and in individuals with speech and hearing disorders. Finally, we discuss the parallels between adult and child tone learning, and provide recommendations concerning how findings in adult tone training can provide insights into tone learning for children by accommodating the needs of individual learners.